2013
DOI: 10.1007/s12663-013-0578-4
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Pattern of Maxillofacial Fractures Seen at a Tertiary Care Hospital in North India

Abstract: Aim The present study was planned to investigate the etiology of maxillofacial injuries and to analyze the pattern of maxillofacial factures as well as the various factors influencing their distribution. Study design A one year cross-sectional study was done and 1,108 patients with maxillofacial fractures were analyzed consecutively from April 2010 to March 2011 who reported to the department of Oral and Maxillofacial Surgery in the Centre for Dental Education & Research and Jai Prakash Narayan Apex Trauma Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 46 publications
4
20
1
Order By: Relevance
“…In our study road traffic accidents are the leading cause of orofacial injuries, which is in consonance with many of the published studies from other parts of India 5 , 6 , 7 , 8 , 9 , 10 and abroad. 11 , 12 , 13 , 14 In contrary to the results of our study, interpersonal violence was the most common cause of orofacial trauma in studies done in New Zealand, 21 North-eastern Brazil, 22 Thailand, 23 United Kingdom, 24 Australia 3 and Zimbabwe.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study road traffic accidents are the leading cause of orofacial injuries, which is in consonance with many of the published studies from other parts of India 5 , 6 , 7 , 8 , 9 , 10 and abroad. 11 , 12 , 13 , 14 In contrary to the results of our study, interpersonal violence was the most common cause of orofacial trauma in studies done in New Zealand, 21 North-eastern Brazil, 22 Thailand, 23 United Kingdom, 24 Australia 3 and Zimbabwe.…”
Section: Discussionsupporting
confidence: 90%
“… 3 The epidemiology of facial injuries varies in injury type, severity and depending upon the population studied. 4 Recent studies from India (Goa, 5 Bhopal, 6 Chennai, 7 Jammu, 8 Gujarat, 9 New Delhi 10 ) and from across the globe (China, 11 Italy, 12 South America, 13 South Korea 14 ) have shown that road traffic accidents are still the primary causes of facial trauma. The causes and pattern of orofacial injuries reflect trauma patterns within the community and, as such, can provide a guide to plan the programmes catered toward prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Also 12 patients wore seat belt and 6 patients did not wear seat belt. These results are consistent with Pandey S et al 27 Many authors have consistently linked alcohol abuse and motor bike accidents 20,21 . Our study revealed 114 patients were under the influence of alcohol at the time of injury.…”
Section: Discussionsupporting
confidence: 92%
“…24 There are many treatment regimens in maxillofacial fracture, but the treatments chosen may differ depending on cost of treatment, affordability, feasibility, patient's willingness to avail the treatments and skill and experience and expertise of operating surgeons. Even though open reduction and internal fixation is gold standard treatment, most of the patients (38.6%) were treated in our institution with closed reduction with arch bar fixation, despite many challenges like malocclusion, asymmetry, nutrition, oral hygiene and pain, our study results are consistent with Marker et al, Worsaae et al and Pandey S et al 25,26,27 and (34.7%) with open reduction and internal fixation (ORIF) with antimicrobial agents. Soft tissue repair/dressing was done in (26.7%) patients.…”
Section: Discussionsupporting
confidence: 88%
“…Similar finding were reported by previously conducted studies. 28,29 Apart from road traffic accidents being more common in our part of the world, high mobility and relative lack of surrounding bony support of the mandibular bone as compared to other facial bones is a contributing factor. However these finding were divergent from the statistics reported from developed countries.…”
Section: Discussionmentioning
confidence: 99%